Between Studying and New Venturing: Personal Knowledge Management Challenges Through the Lens of Entrepreneurship Undergraduate Students - Najmi Shaumi Mumtaz; Jann Hidajat Tjakraatmadja (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2022)
Research to improve entrepreneurship education in higher educational institutions (HEIs) has gained much attention over the past years. Prior studies have thoroughly investigated the challenges of entrepreneurship education based on the providers' and educators’ perspectives. However, the experiences of the students who receive and undergo the process have not received equal attention, especially when investigating the "for" entrepreneurship approach where the goal is to develop entrepreneur graduates. Thus, a phenomenological study was conducted to understand the challenges that the students perceive in studying entrepreneurship whilst creating their businesses as the expected outcome of the "for" entrepreneurship approach. The data gathered from six participants from an undergraduate entrepreneurship program revealed that their struggles were related to personal knowledge management practices. This finding extends the literature on entrepreneurship education and presents avenues for further inquiry on personal knowledge management for entrepreneurship education.